Towards an ontology-based recommender system for agile practices adoption - Roldán, M. Luciana; Bollati, Verónica A.; Gonnet, Silvio M. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de Software, 2022)
Choosing the right agile practices to be adopted in a software development process is complex, especially for organizations with little experience and a high turnover of human resources. To select the best practices, it is necessary to consider the characteristics that describe the team, the project, and the context in which they will be applied. In this paper, we propose an ontology-based agile practices recommender. The ontology was built and populated with knowledge obtained from software projects of Argentine organizations. The recommender applies the FP-Growth algorithm to find the most suitable practices for the target profile. In addition, it discovers potential conflicts between the profile and the recommended practices.